STUDY OF EXTRACTS OF NATURAL MATERIALS AS ALUMINUM GREEN INHIBITORS AND ITS ALLOYS IN CHLORIDE ACID SOLUTIONS AND SODIUM HYDROXIDE: A CRITICAL REVIEW - Luc Gutomo, William
Aluminum is one of most used metal. Although it has good corrosion resistance in the atmosphere and in some aqueous environments, aluminum can undergo corrosion when used in strong acids and strong bases. One example of the use of aluminum in an acidic environment is the pickling process. While one example of using aluminum in alkaline solutions is as an anode material in aluminum-air batteries. Inhibitors are one of the most commonly used solutions to overcome the negative effects of corrosion. However, when they accumulate in nature, conventional inhibitors have a toxic effect. Researchers are trying to find alternative inhibitors from natural ingredients to prevent enviromental issues. In this literature study, several extracts of natural ingredients were studied for their inhibitory effects on aluminum and its alloys in hydrochloric acid and sodium hydroxide solutions. The data used in this review is a collection of literature on corrosion testing from research on extracts of natural materials as aluminum inhibitors for the past 11 years. The variation of inhibitor concentration and temperature in the weight loss test was carried out to study the effect of inhibitor concentration and temperature on inhibitor efficiency. The Tafel extrapolation test is performed to determine the type of inhibitor (cathodic, anodic, or mixed). The EIS test was performed to determine the inhibition mechanism. Meanwhile, the gasometric test was used to determine the corrosion mechanism. Literature study data show that extracts of natural materials were able to reduce the corrosion rate of aluminum and its alloys in HCl and NaOH solutions. The inhibitor efficiency of each extract ranged from 69.95% to 97.04%. Based on the Cdl and Rct data in the EIS test, it is known that the inhibitor is adsorbed on the aluminum surface and reduces its contact area with water molecules which results in a reduced corrosion rate. The adsorption mechanism can be determined by the ?Gads value obtained through the Arrhenius plot. The value of ?Gads obtained ranged from -7.13 kJ / mol to -35.11 kJ / mol. This indicates that the inhibitor is adsorbed on the surface of the aluminum by a combination of the physical absorption and chemisorption mechanisms. Increasing the inhibitor concentration increases the efficiency of the inhibitor to a critical concentration. After surpassing the critical concentration, increasing the inhibitor concentration becomes ineffective. The increase in temperature causes the weakening of the inhibitor adsorption bonds which causes a decrease in the efficiency of the inhibitor. Inhibitor efficiency is influenced by the content of the extract compound. All extracts have lone pairs from heteroatoms and ? electrons from double bonds in aromatic compounds, which in theory is one of the requirements for an effective organic inhibitor.